(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Thebes has came into existence (the current city of Luxor) as a village of the upper villages of Egypt since the third alpha B.C, where the old Egyptian human inhabited it and during the Egyptian dynasties it occupied an important role in the history of Egypt on its expansion. during the old government era Thebes was still a simple village and Amun was a little important local god, where the desting of Thebes and its god Amun connected together from power and sthenia, when the rulersʼs strength of Thebes glorified during the middle government era to expansion in both upper and lower Egypt. So it grew the authority of Amun and He became the first national god and when the rulers of Thebes lead the struggle war against the Hyksos, the god Amun became the resistence god and with the extraneous Egyptian expansion which followed the removing of the Hyksos and its yield the building of the Egyptian empire in Syria during the modern government era, Amun, the god became the global god and the kings of Egypt indebted to the god Amun of their success and this show during of His much having from the income of His temples and in opposition Amun gave generously of his blessing on the dead kings who bury in the graveyards of Thebes